THE USE OF FINANCIAL MANAGEMENT PRACTICE BY BATIK PEKALONGAN MSMEs - Moch Luthfi; Ellen Rusliati (Jurnal Riset Bisnis dan Manajemen, 2020)
Micro, Small, and Medium Enterprises (MSMEs) are recognized worldwide as the main source of dynamism, innovation, and flexibility. This study aims to analyze the financial management practices used by the Pekalongan batik craft SMEs. The method used is descriptive with a qualitative approach. Data were collected by structured interviews with a samples are 30 determind by snowwball sampling. The results show that the owner’s knowledge of financial management is still limited, did not prepared a financial budget regularly, and rarely compare the budget with the actual results. Most owners had check supplies once a week and did not evaluate the feasibility before started to invest. Range for ROA were 2% to 5%, and NPM 10% to 20%. All owners are satisfied with doing the business, and no one to thinks of moving to other businesses in other fields.